Flame retardant low-density polyethylene composite material and preparation method and application thereof
By using modified ammonium polyphosphate and char-forming agent in low-density polyethylene to form an intumescent flame retardant system, the problem in the existing technology that the improvement of flame retardant performance leads to a decrease in mechanical properties is solved, and efficient flame retardant performance and stable mechanical properties.
Patent Information
- Application Number
- CN202410516925.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-26
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-04-26
AI Technical Summary
When the prior art improves the flame retardant properties of low-density polyethylene, it usually leads to a decrease in the mechanical properties of the material and there is a problem of melting drops during combustion.
An intumescent flame-retardant system is formed by using modified ammonium polyphosphate and char-forming agent coated with organosiloxane compounds and silicone gel, and intumescent flame-retardant low-density polyethylene composite materials are prepared through melt blending.
While ensuring the stable mechanical properties of the material, the flame retardant properties of low-density polyethylene are improved to meet flame retardant requirements, the amount of smoke released is reduced, and the problem of molten droplets is solved.
Smart Images

Figure BDA0004816977590000131 
Figure BDA0004816977590000132 
Figure BDA0004816977590000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame retardant materials, and in particular to a flame retardant low-density polyethylene composite material and a preparation method and application thereof. Background Art
[0002] With the rapid development of electronic appliances, building materials, transportation and other fields, the demand for flame retardant materials is growing. Traditional flame retardants may produce toxic and harmful gases during use, which does not meet the current environmental protection requirements. Therefore, the research and development of environmentally friendly flame retardants has become a hot topic in the field of scientific research. Low-density polyethylene (LDPE) is a commonly used plastic material. Due to its good processing properties, it has been widely used in many fields such as packaging, agriculture, construction, automobiles, wires and cables, etc., and the research on its flame retardant properties is particularly important.
[0003] One of the simplest ways to improve the flame retardancy of LDPE is to add flame retardants. The most common flame retardants are halogen-based flame retardants, inorganic flame retardants or intumescent flame retardants. Halogen-based flame retardants have excellent flame retardant properties, but they produce highly toxic gases when burned and are not accepted by the environment. Inorganic flame retardants have the characteristics of good stability, low toxicity, non-toxicity, no corrosive gases and long-term flame retardant effects, but in order to make LDPE have higher flame retardancy, the amount of inorganic flame retardants must be increased. Due to the incompatibility of inorganic fillers and organic materials, the large amount of inorganic flame retardants added can ensure the flame retardancy of LDPE, but the mechanical properties of LDPE will be greatly reduced. Intumescent Flame Retardant (IFR) is composed of P, N, and C as core components. After thermal decomposition, it can form an expanded porous protective carbon layer on the polymer surface, inhibiting heat and oxygen transfer, reducing the production of combustibles, and inhibiting polymer droplets, so that the polymer can achieve effective flame retardancy while ensuring stable mechanical properties. It is non-toxic, low-smoke, halogen-free, and fully meets environmental protection requirements. Therefore, how to improve flame retardant efficiency, inhibit polymer droplets, reduce production costs, and expand application areas without affecting mechanical properties is a key issue that must be solved in the future.
[0004] In view of this, this invention is proposed. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems existing in the prior art and provide a flame retardant low-density polyethylene composite material and a preparation method and application thereof, so as to improve the flame retardant properties of low-density polyethylene while ensuring that the mechanical properties of the low-density polyethylene are not sacrificed as much as possible, and solve the problem of molten droplets dripping during combustion.
[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a flame-retardant low-density polyethylene composite material composition, wherein the composition comprises the following components by mass percentage: 55-85% low-density polyethylene, 10-25% modified ammonium polyphosphate and 5-20% carbon-forming agent;
[0007] Wherein, the modified ammonium polyphosphate is ammonium polyphosphate coated with an organic siloxane compound and a silicone gel.
[0008] The second aspect of the present invention provides a flame retardant low-density polyethylene composite material prepared from the composition described in the first aspect.
[0009] The third aspect of the present invention provides a method for preparing the flame-retardant low-density polyethylene composite material described in the second aspect, wherein the method comprises: melt-blending low-density polyethylene, modified ammonium polyphosphate and a carbon-forming agent to obtain the flame-retardant low-density polyethylene composite material.
[0010] The fourth aspect of the present invention provides the use of the flame-retardant low-density polyethylene composite material described in the second aspect or the flame-retardant low-density polyethylene composite material obtained by the preparation method described in the third aspect in wires and cables.
[0011] Through the above technical solution, the beneficial technical effects achieved by the present invention are as follows:
[0012] The present invention uses an organic siloxane compound and ammonium polyphosphate coated with silicone gel and a carbon forming agent to form an intumescent flame retardant system, and prepares an intumescent flame retardant low-density polyethylene composite material through melt blending. The oxygen index of the product can meet the flame retardant requirements and reduce the amount of smoke released, while solving the problem that the addition of flame retardants in the prior art will greatly reduce the mechanical properties of the material. The mechanical properties of the intumescent flame retardant low-density polyethylene composite material product prepared by the present invention remain stable. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 Infrared spectra of THEIC, Si-THEIC and Si-THEIC@Si-APP;
[0014] Figure 2 SEM images of APP, THEIC, Si-THEIC and Si-THEIC@Si-APP. DETAILED DESCRIPTION
[0015] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0016] The first aspect of the present invention provides a flame retardant low-density polyethylene composite material composition, wherein the composition comprises the following components in percentage by mass: 55-85% low-density polyethylene, 10-25% modified ammonium polyphosphate and 5-20% carbon-forming agent;
[0017] Wherein, the modified ammonium polyphosphate is ammonium polyphosphate coated with an organic siloxane compound and a silicone gel.
[0018] In the present invention, the modified ammonium polyphosphate is ammonium polyphosphate doubly coated with an organic siloxane compound and a silicone gel.
[0019] In some embodiments of the present invention, the mass percentage of the low-density polyethylene is 55-85%, preferably 65-75%.
[0020] In some embodiments of the present invention, the mass percentage of the modified ammonium polyphosphate is 12-20%.
[0021] In some embodiments of the present invention, the mass percentage of the char-forming agent is 10-18%.
[0022] In some embodiments of the present invention, the carbon-forming agent is selected from at least one of tris(2-hydroxyethyl)isocyanurate (THEIC), CFA, melamine cyanurate (MCA) and pentaerythritol (PER), preferably tris(2-hydroxyethyl)isocyanurate (THEIC).
[0023] In some embodiments of the present invention, the preparation method of the modified ammonium polyphosphate (continuous sol-gel method) comprises the following steps:
[0024] (1) allowing a triazine compound and a siloxane modifier to react in a solvent-free manner to obtain an organosiloxane compound;
[0025] (2) ammonium polyphosphate (APP), an organic solvent and water are mixed, the pH is adjusted to alkaline, and then an emulsifier, a silicate and the organosiloxane compound obtained in step (1) are added respectively to react to obtain modified ammonium polyphosphate.
[0026] In some embodiments of the present invention, the reaction temperature in step (1) is 130-140°C, preferably 140°C.
[0027] In some embodiments of the present invention, in step (1), the triazine compound and the siloxane modifier are mixed in an oil bath.
[0028] In some embodiments of the present invention, the pH is adjusted to 8.5 in step (2).
[0029] In some embodiments of the present invention, in step (2), the reaction product is washed, filtered, and dried to obtain modified ammonium polyphosphate.
[0030] In some embodiments of the present invention, the triazine compound is selected from at least one of tris(2-hydroxyethyl)isocyanurate (THEIC), melamine (ME) and hydroxyethylhexahydro-s-triazine, preferably tris(2-hydroxyethyl)isocyanurate (THEIC).
[0031] In some embodiments of the present invention, the siloxane modifier is selected from at least one of γ-isocyanate propyl triethoxy silane (IPTES), γ-aminopropyl triethoxy silane (KH-550), vinyl trimethoxy silane (A-171) and vinyl triethoxy silane (A-151), preferably γ-isocyanate propyl triethoxy silane (IPTES).
[0032] In some embodiments of the present invention, the organic solvent is selected from at least one of ethanol, methanol, acetone and dimethylformamide (DMF).
[0033] In some embodiments of the present invention, the pH adjusting agent used to adjust the pH is selected from at least one of a NaOH aqueous solution, triethanolamine and ammonia water.
[0034] In some embodiments of the present invention, the emulsifier is selected from at least one of OP-10, AEO-9, DC-106, TERGITOL CA series, ECOSURF EH series, TERGITOL 15-S and emulsifier Berol 185 series;
[0035] In some embodiments of the present invention, the silicate is selected from at least one of methyl orthosilicate, tetraethyl orthosilicate (TEOS), propyl orthosilicate and butyl orthosilicate.
[0036] According to a particularly preferred embodiment of the present invention, the preparation method of the modified ammonium polyphosphate comprises the following steps:
[0037] (1) fully mixing THEIC and IPTES, and reacting them without solvent at the melting temperature of THEIC to obtain an organosiloxane compound Si-THEIC;
[0038] (2) ammonium polyphosphate, ethanol and water are mixed, the pH is adjusted to alkaline, and then an emulsifier, TEOS and the organosiloxane compound obtained in step (1) are added respectively to react to obtain a white solid powder, which is ammonium polyphosphate Si-THEIC@Si-APP coated with the organosiloxane compound and silica gel.
[0039] The second aspect of the present invention provides a flame retardant low-density polyethylene composite material prepared from the composition described in the first aspect.
[0040] The third aspect of the present invention provides a method for preparing the flame-retardant low-density polyethylene composite material described in the second aspect, the method comprising: melt-blending low-density polyethylene, modified ammonium polyphosphate and a carbon-forming agent to obtain the flame-retardant low-density polyethylene composite material.
[0041] The invention puts low-density polyethylene, modified ammonium polyphosphate and a carbon-forming agent into an internal mixer, and mixes them uniformly through sufficient extrusion and shearing in a molten state.
[0042] In some embodiments of the present invention, the melt blending conditions include: a temperature of 155-165° C. and a time of 10-15 min.
[0043] The fourth aspect of the present invention provides the use of the flame-retardant low-density polyethylene composite material described in the second aspect or the flame-retardant low-density polyethylene composite material obtained by the preparation method described in the third aspect in wires and cables.
[0044] The present invention will be described in detail below through examples.
[0045] In the following examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be obtained through commercial channels.
[0046] In the embodiments and comparative examples, the ammonium polyphosphate is type II ammonium polyphosphate (DP>1000, industrial grade, Jinan Taixing Fine Chemical Co., Ltd.), the mass fraction of ethanol is 95%, the purity of ammonia water is ≥99%, and the low-density polyethylene is model 3518CB and has a density of 0.91-0.93 g / cm 3 The polyethylene resin material of THEIC has a purity of ≥98% and a vacuum degree of 0.09MPa for vacuum drying.
[0047] Si-THEIC@Si-APP was prepared as follows:
[0048] First, THEIC and IPTES are reacted without solvent at the melting temperature of THEIC to obtain an organosiloxane compound (Si-THEIC);
[0049] Then, ammonium polyphosphate, ethanol and water were mixed, the pH was adjusted to 8.5 with aqueous ammonia, and OP-10, TEOS and Si-THEIC were added respectively to react to obtain a white solid powder, namely Si-THEIC@Si-APP.
[0050] MCAPP was prepared according to the following steps:
[0051] First, A-151 is subjected to a solvent-free reaction at the melting temperature of THEIC to obtain an organosiloxane compound;
[0052] Then, ammonium polyphosphate, ethanol and water are mixed, and the pH is adjusted to 8.5 with aqueous ammonia. Then, OP-10, TEOS and an organic siloxane compound are added respectively to react to obtain a white solid powder, namely MCAPP.
[0053] Si-APP was prepared according to the following steps:
[0054] Ammonium polyphosphate, ethanol and water are mixed, the pH is adjusted to 8.5 with ammonia water, and OP-10 and TEOS are added to react to obtain a white solid powder, which is Si-APP.
[0055] UF-APP was prepared as follows:
[0056] 5.0 g of urea and 10.0 g of formaldehyde solution were placed in a 100 mL three-necked flask, and 50 mL of water was then added. Next, the pH of the mixture was adjusted to 8.5 with a 10% triethanolamine solution. The mixture was then immediately mechanically stirred in an 80 ° C oil bath until it became clear. Finally, the clear prepolymer solution was cooled to room temperature to obtain a urea-formaldehyde resin prepolymer (UF).
[0057] 50.0 g APP, 100 mL ethanol and 50 mL deionized water were added to a 500 mL three-necked round-bottom flask, and the pH was adjusted to 10.0 with triethanolamine. Then, 1.0 g OP-10 was added, and the temperature was raised to 40 ° C. The reactants were stirred at 500 rpm for 10 min, the UF prepolymer solution was added dropwise to the suspension, the pH was adjusted to 5.0 with acetic acid, and then the reaction was carried out at 80 ° C for 2 hours. Finally, the mixture was cooled to room temperature, filtered, washed three times with ethanol, and vacuum dried at 100 ° C to obtain a white solid powder, named UF-APP.
[0058] Example 1
[0059] This example is used to illustrate the preparation of a flame retardant low-density polyethylene composite material.
[0060] 70% low-density polyethylene (LDPE), 18% Si-THEIC@Si-APP, and 12% THEIC were placed in an oven at 60 °C for 12 h to dry and remove water;
[0061] Preheat the internal mixer to 155℃, wait for the temperature to stabilize, then slowly add low-density polyethylene, then slowly add Si-THEIC@Si-APP and THEIC, so that all the raw materials are fully extruded and sheared in the internal mixer and mixed evenly. After mixing for 10 minutes, the flame-retardant low-density polyethylene composite material product is obtained.
[0062] Example 2
[0063] This example is used to illustrate the preparation of a flame retardant low-density polyethylene composite material.
[0064] 70% low-density polyethylene (LDPE), 20% Si-THEIC@Si-APP, and 10% THEIC were placed in an oven at 60°C for 12 h to dry and remove water;
[0065] Preheat the internal mixer to 162℃, and after the temperature stabilizes, slowly add low-density polyethylene. After the low-density polyethylene is added, slowly add Si-THEIC@Si-APP and THEIC to make all the raw materials fully extruded, sheared and mixed in the internal mixer. After mixing for 13 minutes, the flame-retardant low-density polyethylene composite material product is obtained.
[0066] Example 3
[0067] This example is used to illustrate the preparation of a flame retardant low-density polyethylene composite material.
[0068] 70% low-density polyethylene (LDPE), 15% Si-THEIC@Si-APP, and 15% THEIC were placed in an oven at 60 °C for 12 h to dry and remove water;
[0069] Preheat the internal mixer to 155℃, wait for the temperature to stabilize, then slowly add low-density polyethylene, then slowly add Si-THEIC@Si-APP and THEIC, so that all the raw materials are fully extruded and sheared in the internal mixer and mixed evenly. After mixing for 10 minutes, the flame-retardant low-density polyethylene composite material product is obtained.
[0070] Example 4
[0071] This example is used to illustrate the preparation of a flame retardant low-density polyethylene composite material.
[0072] 70% low-density polyethylene (LDPE), 12% Si-THEIC@Si-APP, and 18% THEIC were placed in an oven at 60 °C for 12 h to dry and remove water;
[0073] Preheat the internal mixer to 160℃, wait for the temperature to stabilize, then slowly add low-density polyethylene, then slowly add Si-THEIC@Si-APP and THEIC, so that all raw materials are fully extruded and sheared in the internal mixer and mixed evenly. After mixing for 15 minutes, the flame-retardant low-density polyethylene composite material product is obtained.
[0074] Example 5
[0075] This example is used to illustrate the preparation of a flame retardant low-density polyethylene composite material.
[0076] 70% low-density polyethylene (LDPE), 10% Si-THEIC@Si-APP, and 20% THEIC were placed in an oven at 60°C for 12 h to dry and remove water;
[0077] Preheat the internal mixer to 160℃, wait for the temperature to stabilize, then slowly add low-density polyethylene, then slowly add Si-THEIC@Si-APP and THEIC, so that all raw materials are fully extruded and sheared in the internal mixer and mixed evenly. After mixing for 15 minutes, the flame-retardant low-density polyethylene composite material product is obtained.
[0078] Example 6
[0079] This example is used to illustrate the preparation of a flame retardant low-density polyethylene composite material.
[0080] 85% low-density polyethylene (LDPE), 10% Si-THEIC@Si-APP, and 5% THEIC were placed in an oven at 60 °C for 12 h to dry and remove water;
[0081] Preheat the internal mixer to 155℃, wait for the temperature to stabilize, then slowly add low-density polyethylene, then slowly add Si-THEIC@Si-APP and THEIC, so that all the raw materials are fully extruded and sheared in the internal mixer and mixed evenly. After mixing for 10 minutes, the flame-retardant low-density polyethylene composite material product is obtained.
[0082] Example 7
[0083] This example is used to illustrate the preparation of a flame retardant low-density polyethylene composite material.
[0084] 80% low-density polyethylene (LDPE), 10% Si-THEIC@Si-APP, and 10% THEIC were placed in an oven at 60°C for 12 h to dry and remove water;
[0085] Preheat the internal mixer to 165℃, wait for the temperature to stabilize, then slowly add low-density polyethylene, then slowly add Si-THEIC@Si-APP and THEIC, so that all raw materials are fully extruded and sheared in the internal mixer and mixed evenly. After mixing for 12 minutes, the flame-retardant low-density polyethylene composite material product is obtained.
[0086] Example 8
[0087] This example is used to illustrate the preparation of a flame retardant low-density polyethylene composite material.
[0088] 75% low-density polyethylene (LDPE), 10% Si-THEIC@Si-APP, and 15% THEIC were placed in an oven at 60 °C for 12 h to dry and remove water;
[0089] Preheat the internal mixer to 165℃, wait for the temperature to stabilize, then slowly add low-density polyethylene, then slowly add Si-THEIC@Si-APP and THEIC, so that all raw materials are fully extruded and sheared in the internal mixer and mixed evenly. After mixing for 12 minutes, the flame-retardant low-density polyethylene composite material product is obtained.
[0090] Example 9
[0091] This example is used to illustrate the preparation of a flame retardant low-density polyethylene composite material.
[0092] 65% low-density polyethylene (LDPE), 25% Si-THEIC@Si-APP, and 10% THEIC were placed in an oven at 60 °C for 12 h to dry and remove water;
[0093] Preheat the internal mixer to 165℃, wait for the temperature to stabilize, then slowly add low-density polyethylene, then slowly add Si-THEIC@Si-APP and THEIC, so that all raw materials are fully extruded and sheared in the internal mixer and mixed evenly. After mixing for 12 minutes, the flame-retardant low-density polyethylene composite material product is obtained.
[0094] Example 10
[0095] This example is used to illustrate the preparation of a flame retardant low-density polyethylene composite material.
[0096] 60% low-density polyethylene (LDPE), 25% Si-THEIC@Si-APP, and 15% THEIC were placed in an oven at 60°C for 12 h to dry and remove water;
[0097] Preheat the internal mixer to 165℃, wait for the temperature to stabilize, then slowly add low-density polyethylene, then slowly add Si-THEIC@Si-APP and THEIC, so that all raw materials are fully extruded and sheared in the internal mixer and mixed evenly. After mixing for 12 minutes, the flame-retardant low-density polyethylene composite material product is obtained.
[0098] Embodiment 11
[0099] This example is used to illustrate the preparation of a flame retardant low-density polyethylene composite material.
[0100] 70% low-density polyethylene (LDPE), 20% MCAPP, and 10% THEIC were placed in an oven at 60°C for 12 h to dry and remove water;
[0101] Preheat the internal mixer to 165℃, wait for the temperature to stabilize, then slowly add low-density polyethylene, then slowly add MCAPP and THEIC, so that all the raw materials are fully extruded and sheared in the internal mixer and mixed evenly. After mixing for 12 minutes, the flame-retardant low-density polyethylene composite material product is obtained.
[0102] Comparative Example 1
[0103] Using 100% low-density polyethylene as the raw material, place it in an oven at 60°C for 12 hours to dry and remove water;
[0104] Preheat the internal mixer to 155°C, and after the temperature stabilizes, slowly add low-density polyethylene to allow the raw materials to be fully extruded and sheared in the internal mixer. After 10 minutes, the low-density polyethylene material product is obtained.
[0105] Comparative Example 2
[0106] A flame retardant low-density polyethylene composite material was prepared according to the method of Example 1, except that the raw materials included 70% low-density polyethylene and 30% THEIC.
[0107] Comparative Example 3
[0108] A flame retardant low-density polyethylene composite material was prepared according to the method of Example 1, except that the raw materials included 70% of low-density polyethylene and 30% of ammonium polyphosphate.
[0109] Comparative Example 4
[0110] A flame retardant low-density polyethylene composite material was prepared according to the method of Example 2, except that Si-THEIC@Si-APP was replaced by unmodified ammonium polyphosphate.
[0111] Comparative Example 5
[0112] A flame retardant low-density polyethylene composite material was prepared according to the method of Example 1, except that the raw materials included 70% of low-density polyethylene and 30% of modified ammonium polyphosphate, and Si-THEIC@Si-APP was replaced by Si-APP.
[0113] Comparative Example 6
[0114] A flame retardant low-density polyethylene composite material was prepared according to the method of Example 1, except that the raw materials included 70% of low-density polyethylene and 30% of modified ammonium polyphosphate, and Si-THEIC@Si-APP was replaced by UF-APP.
[0115] Comparative Example 7
[0116] A flame retardant low-density polyethylene composite material was prepared according to the method of Example 2, except that Si-THEIC@Si-APP was replaced by UF-APP.
[0117] Comparative Example 8
[0118] A flame retardant low-density polyethylene composite material was prepared according to the method of Example 1, except that the raw materials included 70% low-density polyethylene and 30% Si-THEIC@Si-APP.
[0119] Test Example 1
[0120] Figure 1 Infrared spectra of APP and Si-THEIC@Si-APP.
[0121] from Figure 1 It can be seen that the characteristic peaks of APP can be found in Si-THEIC@Si-APP. 3000-3500cm -1 The peak intensity of -NH and NH4 + Characteristic peak, 1020cm -1 Corresponding to the stretching vibration of PO2 and PO3, 1253 cm -1 and 1079cm -1 The symmetrical stretching vibrations of the P=O and PO bonds are 886 cm -1 and 802cm -1 The asymmetric stretching vibrations of the PO and POP bonds are at 1467 cm -1 The absorption peak of CN is increased at 1106cm -1 and 1250cm -1 The characteristic absorption peaks of Si-O-Si and Si-OC appeared, indicating that ammonium polyphosphate was successfully modified.
[0122] Figure 2SEM images of APP, THEIC, Si-THEIC and Si-THEIC@Si-APP.
[0123] Depend on Figure 2 It can be seen that the surface of unmodified APP is relatively smooth and angular, while the surface of APP modified by Si-THEIC becomes rougher and a large number of silicon spheres are attached.
[0124] Test Example 2
[0125] The flame-retardant low-density polyethylene composite materials prepared in Examples 1-11 and Comparative Examples 1-8 were subjected to relevant tests of vertical combustion and limiting oxygen index. The test results are shown in Tables 1 and 2.
[0126] Table 1 Flame retardant performance test results of Examples 1-11
[0127]
[0128] Table 2 Flame retardant performance test results of comparative examples 1-8
[0129]
[0130] The vertical combustion test was conducted according to the American National Standard UL-94 (ANSI / ASTMD635-77), and the size of each sample was 125×12.5×3.2mm. In the evaluation level, V-0 means that the vertical sample stops burning within 10s, and no droplets are allowed; V-1 means that the vertical sample stops burning within 30s, and no droplets are allowed; V-2 means that the vertical sample stops burning within 30s, and dripping of burning materials is allowed; NR means no level.
[0131] The limiting oxygen index is measured using an oxygen index meter in accordance with the American national standard LOI (ASTM D2863-97). The size of each sample is 120×6.5×3.2mm. This project tests the minimum oxygen concentration when the material just maintains balanced combustion. For flame retardant materials, the higher the index, the better.
[0132] As can be seen from Tables 1 and 2, the present invention forms an intumescent flame retardant system through Si-THEIC@Si-APP or MCAPP and a carbon-forming agent, and prepares an intumescent flame retardant low-density polyethylene composite material through melt blending, which has good flame retardant properties, reaches V-0 grade and has no molten droplets. Therefore, the intumescent flame retardant low-density polyethylene composite materials prepared in Examples 1-11 of the present application can all be called flame retardant materials. The flame retardant material stands out for its excellent flame retardant properties, and its limiting oxygen index is better than similar products. This feature gives it a significant advantage in high-demand flame retardant occasions. This means that under the same environmental conditions, the flame retardant material can more effectively resist the spread of flames than other products, providing higher safety guarantees for application scenarios.
[0133] Test Example 3
[0134] The flame-retardant low-density polyethylene composite materials prepared in Examples 1-11 and Comparative Examples 1-8 were subjected to relevant tests on tensile strength and elongation at break. The test results are shown in Tables 3 and 4.
[0135] The tensile strength and elongation at break tests were performed using a universal material testing machine with reference to the national standard GB / T1040.2-2006. The elongation at room temperature was 20±2 mm / min. The size of each specimen was a dumbbell shape of 2×4 mm. Each specimen was measured 5 times to obtain the average value.
[0136] Table 3 Mechanical properties test results of Examples 1-11
[0137]
[0138] Table 4 Mechanical properties test results of comparative examples 1-8
[0139]
[0140] It can be seen from Tables 3 and 4 that the tensile strength and elongation at break of the prepared expanded flame retardant low-density polyethylene composite product are indeed reduced compared with pure LDPE and other flame retardant materials by improving the components of the present invention. This is due to the addition of flame retardants and the effect of the expanded flame retardant mechanism, rather than the defects of the material itself. However, the expanded flame retardant LDPE composite material of the embodiment has sufficient mechanical properties to meet the requirements of specific applications.
[0141] In summary, the present invention forms an intumescent flame retardant system through Si-THEIC@Si-APP or MCAPP and a carbon-forming agent. APP, as an acid source, can release acidic substances such as phosphoric acid or metaphosphoric acid during combustion. These acidic substances can promote the formation and stabilization of the carbon layer; in addition, it can also provide a small amount of gas source. The modified THEIC is used as a carbon source because it can decompose at high temperatures to produce carbonaceous residues. IPTES provides a silicon source and, as a siloxane modifier, chemically bonds with organic substances such as THEIC through a silane bonding reaction to enhance the bonding force between the flame retardant and the substrate. These components work together to form an intumescent flame retardant system, and an intumescent flame retardant low-density polyethylene composite material is prepared by melt blending, which has good flame retardant properties, reaches V-0 grade and has no molten droplets. The product has excellent performance in limiting oxygen index, meets the flame retardant requirements and reduces the amount of smoke released, making it a leader in the field of fire safety. The mechanical properties remain within the applicable range and can be used in specific scenarios to provide users with more reliable and safe protection.
[0142] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A flame retardant low-density polyethylene composite material composition, characterized in that: The composition comprises the following components in percentage by mass: 55-85% of low-density polyethylene, 10-25% of modified ammonium polyphosphate and 5-20% of a carbon-forming agent; Wherein, the modified ammonium polyphosphate is ammonium polyphosphate coated with an organic siloxane compound and a silicone gel; The preparation method of the modified ammonium polyphosphate comprises the following steps: (1) reacting a triazine compound and a siloxane modifier in a solvent-free manner to obtain an organosiloxane compound; (2) ammonium polyphosphate, an organic solvent and water are mixed, the pH is adjusted to alkaline, and then an emulsifier, a silicate and the organosiloxane compound obtained in step (1) are added respectively to react to obtain modified ammonium polyphosphate.
2. The composition according to claim 1, wherein The mass percentage of the low-density polyethylene is 65-75%; And / or, the mass percentage of the modified ammonium polyphosphate is 12-20%; And / or, the mass percentage of the carbon-forming agent is 10-18%; And / or, the carbon-forming agent is selected from at least one of tris(2-hydroxyethyl)isocyanurate, CFA, melamine cyanurate and pentaerythritol.
3. The composition according to claim 1, wherein The carbon-forming agent is tris(2-hydroxyethyl)isocyanurate.
4. The composition according to claim 1, wherein The reaction temperature in step (1) is 130-140°C; and / or, in step (1), the triazine compound and the siloxane modifier are mixed in an oil bath; and / or, in step (2), adjusting the pH to 8.5; And / or, in step (2), the reaction product is washed, filtered, and dried to obtain modified ammonium polyphosphate.
5. The composition according to claim 1, wherein The reaction temperature in step (1) is 140°C.
6. The composition according to claim 1, wherein The triazine compound is selected from at least one of tris(2-hydroxyethyl)isocyanurate, melamine and hydroxyethylhexahydro-s-triazine; And / or, the siloxane modifier is at least one selected from γ-isocyanate propyl triethoxy silane, γ-aminopropyl triethoxy silane, vinyl trimethoxy silane and vinyl triethoxy silane.
7. The composition according to claim 1, wherein The triazine compound is tris(2-hydroxyethyl)isocyanurate; And / or, the siloxane modifier is γ-isocyanate propyltriethoxysilane.
8. The composition according to claim 1, wherein The organic solvent is selected from at least one of ethanol, methanol, acetone and dimethylformamide; and / or, the pH adjusting agent used for adjusting the pH is selected from at least one of a NaOH aqueous solution, triethanolamine and ammonia water; and / or, the emulsifier is at least one selected from OP-10, AEO-9, DC-106, TERGITOL CA series, ECOSURF EH series, TERGITOL 15-S and emulsifier Berol 185 series; And / or, the silicate is selected from at least one of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate and butyl orthosilicate.
9. A flame retardant low-density polyethylene composite material prepared from the composition according to any one of claims 1 to 8.
10. A method for preparing the flame-retardant low-density polyethylene composite material according to claim 9, characterized in that: The method comprises: melt-blending low-density polyethylene, modified ammonium polyphosphate and a carbon-forming agent to obtain a flame-retardant low-density polyethylene composite material.
11. The method according to claim 10, wherein: The melt blending conditions include: temperature of 155-165° C. and time of 10-15 min.
12. Use of the flame-retardant low-density polyethylene composite material according to claim 9 or the flame-retardant low-density polyethylene composite material obtained according to the preparation method according to claim 10 or 11 in wires and cables.
Citation Information
Patent Citations
Preparation method for thermal-stability anti-dripping flame retardant
CN107880316A
Flame-retardant low-density polyethylene composite material and preparation method thereof
CN117736508A